Silver polyvinyl pyrrolidone nanoparticles exhibit a capsular polysaccharide influenced bactericidal effect against Streptococcus pneumoniae - Bibbs, Ronda K.; Harris, Rhonda D.; Peoples, Veolanda A.; Barnett, Cleon; Singh, Shree R.; Dennis, Vida A.; Coats, Mamie T. (Frontiers in Microbiology, 2014)
Streptococcus pneumoniae remains a leading cause of morbidity and mortality worldwide. The highly adaptive nature of S. pneumoniae exemplifies the need for next generation antimicrobials designed to avoid high level resistance. Metal based nanomaterials fit this criterion. Our study examined the antimicrobial activity of gold nanospheres (AuNP), silver coated polyvinyl pyrrolidone (AgPVP), and titanium dioxide (TiO2) against various serotypes of S. pneumoniae. Twenty nanometer spherical AgPVP demonstrated the highest level of killing among the tested materials. AgPVP (0.6 mg/mL) was able to kill pneumococcal serotypes 2, 3, 4, and 19F within 4 hours of exposure. Detailed analysis of cultures during exposure to AgPVP showed that both the metal ions and the solid nanoparticles participate in the killing of the pneumococcus. The bactericidal effect of AgPVP was lessened in the absence of the pneumococcal capsular polysaccharide. Capsule negative strains, JD908 and RX1, were only susceptible to AgPVP at concentrations at least 33% higher than their respective capsule expressing counterparts. These findings suggest that mechanisms of killing used by nanomaterials are not serotype dependent and that the capsular polysaccharide participates in the inhibition. In the near future these mechanisms will be examined as targets for novel antimicrobials.